OPTIMALISASI HIDROLISIS SUKROSA MENGGUNAKAN RESIN PENUKAR KATION TIPE SULFONAT - Razak, Abd. Rahman Razak; Sumarni, Ni Ketut; Rahmat, Basuki (Natural Science: Journal of Science and Technology, 2012)
Optimization of sucrose hydrolysis has been investigated by using a sulfonic type cation excange. The aim of investigation are to find out the effect of resin concentration, agitation time and the recycling of resin without ion excange treatment with optimum condition for the effectiveness of resin as catalys in hydrolysis of sucrose 70%. The result, there were obtained that the optimum condition in hirolysis of sucrose occurred at 30 grams of resin and agitation time at 16 hours, the product of sugar invert was 833.810 mg or 1.132%. The recycled of resin without ion treatment on the optimum condition as catalys in hidrolysis sucrose affected to the reduction of resin effectiveness. From Duncan?s test, the best effectiveness recycling of resin without ion treatment on the optimum condition are four time